WASTE BANKS OPTIMIZATION IN THE FRAMEWORK OF REALIZING IT ECO-GREEN IN PACIRAN LAMONGAN VILLAGE - Nurus Safaatilllah; Ruswaji Ruswaji; Ratna Handayati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Garbage is one of the social problems faced by everyone, both in villages and cities. According to Slamet (2002) waste is the residue of human daily activities or it can also be natural processes in the form of solid, or semi-solid in the form of organic or inorganic substances that can be decomposed and cannot be decomposed which are considered useless and disposed of into the environment. Indonesian Ministry of Environment. issued data on the average population living and living in Indonesia which generates 0.8 kg of waste or the equivalent of 200 million kg/day of the total population. The main source of waste in Indonesia is households, which nationally account for 44% of the total waste generation. Poor waste management in the form of garbage disposal on riverbanks, coasts and waterways is the main cause of flooding in Paciran village and its surroundings. Like the recent incident, the water discharge increased and overflowed during heavy rains. This was caused by piles of garbage that blocked the flow of river water. To overcome all this, it is necessary to strive to provide supporting facilities for waste handling so that people do not throw garbage into rivers and onto beaches, so a Garbage Bank was established. A waste bank is a place for collecting waste that has been sorted where the results of the collection will be deposited in a garbage collector. The purpose of the garbage bank is not only to overcome flooding and to maintain the beauty of the beach which is a tourist spot in Paciran village, but also to increase the income of the local community in the midst of a pandemic that has affected the community's economy. every customer account registered in the Garbage Bank. In addition to being deposited in collectors, some trash is also recycled into handicrafts with economic value such as bags, pots, piggy banks etc.. Utilizers of waste are turned into handicrafts and become regional souvenir icons for tourists.